Building SOA-based composite applications using NetBeans IDE 6 : design, build, test, and debug service-oriented applications with ease using XML, BPEL, and Java web services /: design, build, test, and debug service-oriented applications with ease using XML, BPEL, and Java web services. (©2008) - Unknown
No abstract available